Sur les chemins d'Onagre : histoire et archéologie orientales : hommage à Monik Kervran - Hardy-Guilbert, Claire,; Renel, Hélène,; Rougeulle, Axelle,; Vallet, Eric,; Kervran, Monik, (Archaeopress archaeology., 2018)
This volume is in honour of Monik Kervran, a pioneer of the French Islamic archaeology in the Middle East. Through the nineteen international contributions found within, the editors and contributors wish to highlight the variety of Monik Kervran's scientific interests.